2016
DOI: 10.1111/spol.12194
|View full text |Cite
|
Sign up to set email alerts
|

Rise of the Regulatory Welfare State? Social Regulation in Utilities in Israel

Abstract: This paper explores the relation between economic liberalization, regulation and welfare. It asks how the state regulates, delays or prevents service disconnection due to debt and arrears, and what this kind of policy implies regarding the use of regulation as a form of social policy. This is done through a comparative study of the electricity and water sectors in Israel after liberalization. It finds that after initial economic reform, both sectors saw a growth in regulation intended to compensate for the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…In recent decades, we have witnessed a major transformation in modern welfare states, with a movement towards the privatisation, decentralisation and commercialisation of social welfare. A new role for government is taking shape, often referred to as the ‘enabling state’ (Gilbert, ), or the ‘regulatory welfare state’ (Benish, Haber, & Eliahou, ; Haber, ; Leisering, ; Levi‐Faur, ). Within this role, instead of directly financing and delivering social welfare goods and services, welfare states increasingly rely on private actors and market‐type arrangements, reshaping the relationships between authorities, private providers and citizens (Ascoli & Ranci, ; Kotkas, ).…”
mentioning
confidence: 99%
“…In recent decades, we have witnessed a major transformation in modern welfare states, with a movement towards the privatisation, decentralisation and commercialisation of social welfare. A new role for government is taking shape, often referred to as the ‘enabling state’ (Gilbert, ), or the ‘regulatory welfare state’ (Benish, Haber, & Eliahou, ; Haber, ; Leisering, ; Levi‐Faur, ). Within this role, instead of directly financing and delivering social welfare goods and services, welfare states increasingly rely on private actors and market‐type arrangements, reshaping the relationships between authorities, private providers and citizens (Ascoli & Ranci, ; Kotkas, ).…”
mentioning
confidence: 99%
“…Our findings suggest that the development of public policy toward philanthropy can be influenced by changes in contextual factors of a state's welfare regime (Anheier & Daly, 2007;Esping-Andersen, 1990). In this study, specifically, public policy toward philanthropy in Israel was shown to be influenced by the establishment of a hybrid, amorphous social welfare regime consisting of social democratic and neoliberal ideological elements (Gal, 2004;Haber, 2011;Lahat & Talit, 2015). Israel is undergoing a transformation from the social-democratic welfare regime that characterized it for many years and is moving fast toward a neoliberal welfare regime that encourages entrepreneurship and a free market.…”
Section: Discussionmentioning
confidence: 92%
“…This shift has facilitated a path for non-state actors to assume leading roles in providing social services. The movement of the Israeli welfare regime toward a liberal or hybrid model created a regulatory role for the state (Gal, 1998(Gal, , 2004Haber, 2011;Levi-Faur, 2014). Thus, the state was defined as navigator rather than rower, and it focused on planning social and educational initiatives.…”
Section: Changes In the Welfare Regime And Government-philanthropy Rementioning
confidence: 99%
“…Responding to recent calls for rapprochement between hitherto largely separate literatures on the "regulatory" and "welfare" state (Haber, 2017;Levi-Faur, 2014), this article explores the role of national welfare state arrangements as an "institutional input" variable (Guidi, Guardiancich, & Levi-Faur, 2020) shaping both the organization of regulatory systems and their preferred instruments for ensuring compliance, that is, "regulatory outputs." To that end, it examines occupational health and safety (OHS) regulation and its relationship to variable arrangements for workers' compensation from a historical institutionalist perspective (Mahoney & Thelen, 2015).…”
Section: Introductionmentioning
confidence: 99%